[OA097] Comparison between skin dose values of a software tool and gafchromic films using test fields and clinical cases. (August 2018) - Rottoli, Federica; De Mattia, Cristina; Sutto, Marina; Colombo, Paola Enrica; Migliorisi, Carmelo; Torresin, Alberto
Abstract : Purpose: To validate the tool for calculation of skin dose absorbed by patients during interventional radiology procedures, which is available in the radiation dose tracking software NEXO[DOSE]® provided by Bracco, Italy. Methods: In NEXO[DOSE], the distribution of skin dose and the peak skin dose (PSD), that is the maximum cumulative dose value resulting from interventional radiology procedures, are displayed and calculated on the surface of a mathematical torso phantom. To determine these quantities, the software uses exposure parameters from Radiation Dose Structured Report and additional information specific of the angiography (table and mattress attenuation, KAP correction factor and tube position relative to the table). To test the accuracy of the algorithm, we irradiated GAFCHROMIC XR-RV3 films wrapped on a cylindrical PMMA phantom with different square fields using two Philips Integris Allura FD20 angiography and a Siemens Artis Zeego. Absolute dose values and geometric accuracy of the phantom dose map calculated by NEXO[DOSE]® were compared with the film. The tool was also clinically tested during high doses interventional procedures by placing a film on the patient's back, at the beam entrance side. Results: In the tested devices, the spatial distribution of the dose estimated by NEXO[DOSE]® was within 10% of the film one. For the dosimetric values, the cumulative dose was in good agreement for high dose fields (<15%) where the deterministic effects are expected. In low-dose region, the discrepancies increase up to 50% probably because the software does not calculate the out-of-field scatter, which is more important in low dose regions. PSD agreement was within 15%. During clinical procedures, films confirmed that the tool can estimate the dose distribution on the patient's skin even for more complex irradiation geometries. In these cases, calculated PSD differs less than the 15% from the film value. Conclusion: NEXO[DOSE]® provides a good estimate of skin dose distribution and PSD. This tool can be useful for the patient follow-up.